Consequences of swidden transitions for crop and fallow biodiversity in southeast asia - Kanok Rerkasem (2018)
Swidden agriculture, once the dominant form of land use throughout the uplands and much of the lowlands of Southeast Asia, is being replaced by other land uses. While change and adaptation are inherent to swiddening, the current rapid and widespread transitions are unprecedented. In this paper we review some recent findings on changes in biodiversity, especially plant diversity at various scales, as swidden farming is replaced by other land uses. We focus particularly on two areas of Southeast Asia: northern Thailand and West Kalimantan. We examine actual and potential changes in the diversity of crops that characterize regional swidden systems, as well as that of the spontaneously occurring plants that appear in swidden fields and fallows. Severe declines in plant diversity have been observed in most areas and at most spatial scales when swidden is replaced by permanent land use systems. However, shifts away from swidden agriculture do not invariably result in drastic declines or losses of biological diversity, but may maintain or even enhance it, particularly at finer spatial scales. We suggest that further research is necessary to understand the effects of swidden transitions on biodiversity. © Springer Science+Business Media, LLC 2009.